Fronto-Temporal Circuits in Musical Hallucinations: A PET-MR Case Study - Cavaliere, Carlo; Longarzo, Mariachiara; Orsini, Mario; Aiello, Marco; Grossi, Dario (Frontiers in Human Neuroscience, 2018)
Aim of the study is to investigate morphofunctional circuits underlying musical hallucinations (MH) in a 72-years old female that underwent a simultaneous 18fluoredeoxyglucose positron emission tomography (PET) and advanced magnetic resonance (MR) exam. This represents a particular case of MH occurred in an healthy subject, not displaying neurological or psychopathological disorders, and studied simultaneously with a multimodal approach. For the resting-state fMRI analysis a seed to seed approach was chosen. For the task-based fMRI, 4 different auditory stimuli were presented. Imaging findings were compared with data obtained by ten healthy controls matched for age and sex. Neuropsychological evaluation and questionnaires investigating depression and anxiety were also administered. PET findings showed hypermetabolism of: superior temporal gyri, anterior cingulate, left orbital frontal and medial temporal cortices. Structural MRI did not show macroscopical lesions except for gliotic spots along the uncinate fascicle pathways with an increased cortical thickness for the right orbitofrontal cortex (p=0.003). DTI showed increased fractional anisotropy values in the left uncinate fascicle, when compared to controls (p=0.04). Resting-state fMRI showed increased functional connectivity between the left inferior frontal gyrus and the left temporal fusiform cortex (p=0.01). Task-based fMRI confirmed PET findings showing an increased activation of the superior temporal gyrus in all the auditory tasks except for the monotone stimulus, with a significant activation of the left orbital frontal cortex only during the song in foreign language, object of MH. Results on cognitive test did not show cognitive impairment, excepting for the performance on Frontal Assessment Battery where the patient fails in the cognitive domains of conceptualization, sensitive to interference and inhibitory control. The subject did not show depressive or anxiety symptoms. Summarizing, multimodal imaging analyses in the MH case showed a microstructural alteration of the left uncinate fascicle paralleled by an increased metabolism and functional connectivity of cortical regions that receive left uncinate projections (orbital frontal cortex, and medial temporal cortex). This alteration of fronto-hyppocampal circuits could be responsible of retrieval of known songs even in the absence of real stimuli.